Pengembangan Kelembagaan untuk Keberlanjutan Proyek (Suatu Studi Kasus pada Proyek Pengadaan Sapi oleh Koperasi Wabita Sri Rejeki Desa Ahuhu Kecamatan Wawotobi Kabupaten Konawe) - Nalefo, La (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2012)
A case study on the impact of institutional development for sustainability of project participants (project sustainability) has been conducted on the asset of Initial Fund Equivalent (MAP), which is facilitated by Cooperative Ministry and UKM of the Indonesian Republic in Ahuhu, Wawotobi district, Konawe regency, Southeast Sulawesi. The study was conducted through a survey of 12 farmer groups by interviewing 60 project participants from members of the group. The result showed that the farmers' institutional performance as project participant is very low. This is evidenced by the low level of participation of respondents in group activities related to counseling, project management, and livestock development. One impact of the weak performance of the participant's project is the inability of the farmer groups to develop economic institution community-based in order to assist the development of farmers livestock. This study proves that one of the causes does not the formation of farmers' economic institutions which is able to take over the project management according to the original plan due to lack of government attention to the institutional development of farmer groups as a coaching container of project participants.